Industrial Sector’s Energy Demand Projections and Analysis of Nepal for Sustainable National Energy Planning Process of the Country - Bhattarai, Nawraj; Bajracharya, Iswor (Journal of the Institute of Engineering, 2016)
The reliable future energy demand projection is an essential requirement for planning and formulating the policy to provide sustainable energy supply in the country. The purpose of this study is to project the sectoral energy demand up to 2030 under different anticipated growth scenarios of national economy. To project future energy demand, the end use industrial sector energy demand model based on Long – range Energy Alternative Planning (LEAP) framework has been formulated with four GDP growth scenarios namely business as usual (BA), low growth (LG), medium growth (MG) and high growth (HG) respectively. Further, the study has illustrated that among the industrial sub-sectors, the energy demand of food beverage and tobacco, textile & leather, chemical rubber & plastics, mechanical engineering & metallurgy and wood products & papers will be increased while the electrical engineering and products subsector will be decreased. Among the anticipated scenarios, the BA scenario has been selected as a reference scenario for policy measures. In the policy scenario, it has been found that the total sectoral energy demand and electricity demand can be reduced from 1.78 and 2.42 times of the base year demand in BA scenario to 1.53 and 2.24 times of the base year demand in 2030 respectively. The projected sectoral energy demand along with demanding fuels will support the sustainable national energy planning process of the country for days to come. Journal of the Institute of Engineering, 2015, 11(1): 50-66